EVOLUTION OF INFORMATION SECURITY TOOLS TO PREVENT ID THEFT IN THE BANKING SECTOR OF PAKISTAN - Amna Abro,; Abdullah Maitlo,; Mumtaz Hussain Mahar, (Spectrum of Engineering Sciences, 2025)
Purpose – Recently information breaches are increased in banking sector of Pakistan. The implementation old and non-effective Information Security Tools to Prevent Identity (ID) Theft pose significant risks to banking sector of Pakistan. The lack of appropriate evolution of these tools in banking sector causes of posing many vulnerabilities in information security infrastructure of and needs to be investigated. The purpose of this paper is to study and investigate the evolution of information security tools to prevent identity theft in banking sector of Pakistan. This paper also identifies the information security weakness in the existing banking infrastructure of Pakistan. Design/methodology/approach – A qualitative case study approach is used to conduct the research. Three case studies are conducted in different banks of Pakistan. The total number of one-to-one semi-structured interviews conducted was 31. A framework for Evolution of Information Security Tools to Prevent ID Theft in banking sector was proposed by extending the guiding framework for knowledge sharing processes for ID theft prevention within organizations proposed by Maitlo et al., (2019). Findings – This research found that Banks need to upgrade their Information security infrastructure. As existing information security tools are not sufficient to prevent identity theft in banking sector of Pakistan. Therefore, it is required to volute the ID Theft Prevention, ID Theft Risk Assessment and ID Fraud Identification Tools. A Managerial Support for Information Security is also required. Practical implications – The research evaluates the information security tools for ID theft prevention in banking sector of Pakistan. It identifies the flaws in information security infrastructure in banking sector and provides the solutions to prevent ID theft. A framework for evolution of the information security tools used to prevent ID theft is developed to strengthen the information security infrastructure of banking sector. It guides the managers for effective use information security tools to empower the information security of banking sector. Originality/value – This study provides a new framework which was developed in the new context to evolute information security tools for ID theft prevention in the banking sector of Pakistan.